Pengaruh Task Commitment dan Locus Of Control terhadap Prestasi Belajar Matematika - Juminah Juminah (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The benefits of the research is to analyze the impacts of task commitment and locus of control on mathematical learning achievement. The method used in this research is survey method with corrasional analysis. The instrument used  is 30 questionnaire and have been  empirically validated. The research used two way Anova analysis and the result show that. First hypothesis, there are interaction impacts of task commitment and locus of control on mathematical learning achievement. Second hypothesis, there are significant impacts of high task commitment and low task commitment on mathematical learning achievement. Third hypothesis, there are significant impacts of internal locus of control and exsternal locus of control on mathematical learning achievement.  Fourth hypothesis show that, a) there are impacts of high task commitment and low task commitment on internal locus of control, b) there are impacts of high task commitment and low task commitment on exsternal locus of control, c) there are significant impacts of internal locus of control and exsternal locus of control on high task commitment, d) there are significant impacts of internal locus of control and exsternal locus of control on low task commitment. So, the writer concluded that there are impacts of both all together and separately between task commitment and locus of control on mathematical learning achievement.